Anti-Thyroid Peroxidase Reactivity Is Heightened in Pemphigus Vulgaris and Is Driven by Human Leukocyte Antigen Status and the Absence of Desmoglein Reactivity - Seiffert-Sinha, Kristina; Khan, Shahzaib; Attwood, Kristopher; Gerlach, John A.; Sinha, Animesh A. (Frontiers in Immunology, 2018)
Pemphigus vulgaris (PV) belongs to an autoimmune disease cluster that includes autoimmune thyroid disease (AITD), suggesting common mechanisms driving autoimmune susceptibility. Our group has shown that PV patients exhibit significant reactivity to AITD-related anti-thyroid peroxidase (TPO), and anti-TPO antibodies affect signaling pathways in keratinocytes similar to anti-desmoglein (Dsg)3 antibodies. To further assess the relevance of anti-TPO reactivity in PV, we analyzed anti-TPO levels in 280 PV and 167 healthy control serum samples across a comprehensive set of variable and static parameters of disease activity and etiopathogenesis. PV patients have significantly higher activity rates for anti-TPO than healthy controls, but levels do not differ between phases of clinical activity and remission. Patients that carry both the PV-associated HLA-alleles DRB1*0402 and DQB1*0503, or DQB1*0503 alone show a low prevalence of anti-TPO (activity rate 9.5% and 4.8%, respectively), while patients that lack expression of these alleles or carry DRB1*0402 alone have a much higher prevalence of anti-TPO (activity rate 23.1% and 15.8%, respectively), suggesting that the absence of DQB1*0503 may predispose patients to the development of anti-TPO antibodies. Similarly, anti-Dsg1-/3- patients have a higher anti-TPO activity rate (26.9%) than anti-Dsg1-/3+ (18.8%), anti-Dsg1+/3- (14.3%) and anti-Dsg1+/3+ (3.9%) patients. Our data suggest that anti-TPO reactivity in PV is driven by genetic markers that may be in linkage disequilibrium with the established PV-susceptibility alleles and that this association drives the selection of a combination of anti-Dsg and anti-TPO antibodies, with anti-TPO filling the gap in active patients that do not carry the established PV-associated autoantibodies and/or are lacking the established PV-HLA-susceptibility alleles.